Experiments in technology forcing: comparing the regulatory processes of US automobile safety and emissions regulations. (1st February 2007) - Gerard, David; Lave, Lester
Technology forcing is a strategy where a regulator mandates a standard that cannot be met with existing technology to internalise external costs associated with the production and/or use of a product. We argue that the implementation process for these policies has a pronounced effect on how regulations affect the development and diffusion of new technologies. To examine this proposition, we look at two case studies of technology forcing policies targeting US automakers: The 1969 Department of Transportation airbag mandate and the 1970 Clean Air Act emissions requirements for new vehicles by 1975. The results of these two mandates were quite different. EPA successfully forced the adoption of catalytic converters, while airbags did not become compulsory for nearly 20 years. We demonstrate that these results did not stem from differences in complexity or costs of adopting the technologies, but instead were a product of political and regulatory variables that influenced the implementation process.